A Reference Model and a vision for manufacturing system for 2030 - Amalnik, Morteza Sadegh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The manufacturing enterprises are now experiencing high pressure of competition. In addition, the advancement in computer software, hardware, networks, information technologies and integration has been gradually reshaping the manufacturing companies by shifting from the industrial age to the information and knowledge era. Due to these elevated competitiveness and advanced computer technology, a number of new manufacturing and management strategies (e.g., Lean production, Just in time, Kaizen, Concurrent Engineering (CE), Cellular Manufacturing (CM), Agile manufacturing, Business process re-engineering (BPR), Agent-based systems (ABS), Computer Integrated Manufacturing (CIM), virtual manufacturing system have emerged for the innovation of manufacturing industries. The developments in organizational concepts created new concepts such as Smart organizations, Centers of excellence, Intelligent enterprises, Integrated enterprises, Virtual enterprises, Virtual enterprises networks, Dynamic enterprises, Extended enterprises, Agile enterprises, Lean enterprises, Process-driven organizations, e-enterprises, Borderless enterprises, Complicated or complex manufacturing systems, Flat structures and others. These terms have been used by researchers to describe various aspects of enterprises and its operational aspects. Although they have different definitions and scopes, there are several common issues: integration of enterprise functions; integration of enterprise resources; and collaboration. In addition Various vendors produced software applications such as Materials Requirement Planning (MRP), Manufacturing Resource Planning (MRP II), Enterprise Resource Planning (ERP),CAD/CAM systems, Manufacturing Execution System (MES), Advanced Planning & Scheduling System (APS), Supply Chain Execution (SCE), Customer Relationship Management (CRM), Advanced Order Management (AOM), Warehouse Management Systems (WMS), Transport Management System (TMS) and others. This paper proposes a Reference Model and vision for Manufacturing System for 2030 and discussed various aspects of future manufacturing enterprise..It supports the inter-enterprise functions/resources integration and collaboration over the networked environment.